Masculinity and modernity in Camilo Castelo Branco - Barcellos, José Carlos (2009)
The aim of this text is to analyze some aspects of the reception of the ideal of modern masculinity in Camilo Castelo Branco’s work; specially, the clash between the latter and previous forms of configuration of masculine gender identity, coming from the aristocratic society.